(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Social Economic Analysis of Fishing Communities in Kedonganan Village, Kuta District, Badung Regency. The fishing community in this study is a community who work as fishermen in Kedonganan Village. The population in this study totaled 211 people who were collected in five groups of fishermen. Sampling in this study used the Slovin formula and was chosen proportionally to represent each area in Kedonganan Village with a total sample of 68 people. The results showed that 89.71% of respondents had a high school level of education, 92.65% of respondents had worked as fishermen for 21-40 years. 61.76% of the dependents of fishermen’s families are 1- 2 people. Apart from being a fisherman, 29.41% of the respondents had a side job. In terms of access to health, it is very easy to reach. Fishermen as a whole have Health Care Insurance (JPK) consisting of a Healthy Indonesia Card (KIS) and Healthy Badung Krama (KBS) to obtain medical services and facilities in all health service centers in Badung Regency. Social conditions of the fishing community in Kedonganan Village, it can be categorized as quite good. NTN for fishing businesses with total income for 2020-2022 are 1.09, 1.10 and 1.08 respectively. The NTN calculation results for fishing businesses on fisheries income are 6.11 in 2020, 6.15 in 2021 and 6.00 in 2022 which is greater than 1. Based on the iNTN calculation results show a value of 100%, 101.21% and 99.45%. The Fishermen’s Exchange Index when viewed from fisheries revenue compared to fisheries expenditure is 100% 100.59% and 98.13%. This means that fishing businesses in Kedonganan Village, Badung in 2020 to 2022 will not experience an increase in catches with costs incurred that are not fixed or fluctuate every year, so that in order to be able to meet the daily needs and expenses of fishing businesses, fishermen need to have side jobs to support the welfare of the people in Kedonganan Village, or fishermen can make efficiency by reducing operational costs so that the income earned can be increased.